Conspiracy hippies and Holocaust denial: The exposure of some contemporary faces of fascism by Center for Political Beauty and Frankfurter Hauptschule - Schultz, Laura Luise (Peripeti, 2023)
While the artists collective Center for Political Beauty address contemporary politicians’ open or tacit denial of Holocaust and the political betrayals of the 1930s in their social interventions, the artists collective Frankfurter Hauptschule expose the intricate entanglements of fascism with hippie-inspired esotericism and a new interest in German Romanticism and Nordic mysticism among young German artists today. The article will analyze the activist practice of the two collectives and discuss what role artistic interventions into politics may play in the fight against the fascist aestheticization of the political in Benjamin’s sense.